Multiomics analyses reveal early metabolic imbalance and mitochondrial stress in neonatal photoreceptors leading to cell death in Pde6brd1/rd1 mouse model of retinal degeneration. Issue 13 (24th January 2022) - Jiang, Ke; Mondal, Anupam Kumar; Adlakha, Yogita K; Gumerson, Jessica; Aponte, Angel; Gieser, Linn; Kim, Jung-Woong; Boleda, Alexis; Brooks, Matthew J; Nellissery, Jacob; Fox, Donald A; Balaban, Robert; et al.
Abstract: Retinal diseases exhibit extensive genetic heterogeneity and complex etiology with varying onset and severity. Mutations in over 200 genes can lead to photoreceptor dysfunction and/or cell death in retinal neurodegeneration. To deduce molecular pathways that initiate and/or drive cell death, we adopted a temporal multiomics approach and examined molecular and cellular events in newborn and developing photoreceptors before the onset of degeneration in a widely-used Pde6b rd1/rd1 ( rd1 ) mouse, a model of autosomal recessive retinitis pigmentosa caused by PDE6B mutations. Transcriptome profiling of neonatal and developing rods from the rd1 retina revealed early downregulation of genes associated with anabolic pathways and energy metabolism. Quantitative proteomics of rd1 retina showed early changes in calcium signaling and oxidative phosphorylation, with specific partial bypass of complex I electron transfer, which precede the onset of cell death. Concurrently, we detected alterations in central carbon metabolism, including dysregulation of components associated with glycolysis, pentose phosphate and purine biosynthesis. Ex vivo assays of oxygen consumption and transmission electron microscopy validated early and progressive mitochondrial stress and abnormalities in mitochondrial structure and function of rd1 rods. These data uncover mitochondrial overactivation and related metabolic alterations as determinants of early pathology and implicate aberrant calcium signaling as an initiator of higher mitochondrial stress. Our studies thus provide a mechanistic framework with mitochondrial damage and metabolic disruptions as early drivers of photoreceptor cell death in retinal degeneration.